Imaging of the articular cartilage repair : Oslikavanje rezultata liječenja zglobne hrskavice - Borić, Igor, liječnik, 1966- (Array, 2020)
Postoperative imaging is necessary for assessing the technical success of the procedure and state of the cartilage healing, as well as for identifying potential complication. A plenty of radiological methods are available today in assessing the articular cartilage: radiography, computed tomography and thomositesis, ultrasonography and magnetic resonance. Radiography is the most used radiological modality but with high limitations in evaluation of the articular cartilage repair. Computed tomography and tomosynthesis are useful only after intraarticular contrast media injection (arthrography) and offer the evaluation of the cartilage surface but with the harmful influence of ionizing radiation. Magnetic resonance (MR) imaging provides non-invasive assessment of the entire joint including evaluation of the cartilage changes and lesions as well as the assessment of the repair site and all other joint tissues. Using compositional MR imaging of cartilage we may get information about its molecular status, specifically in regard to its collagen and glycosaminoglycan content. This article is a review of all imaging methods, in cartilage repair evaluation stressing novel imaging methods representing their advantages and limitations in cartilage repair evaluation.